Miniature nuclear magnetic resonance spectrometer using a partially enclosed permanent magnet. Issue 3 (4th May 2017) - Lu, Rongsheng; Zhou, Xinlong; Yin, Qifeng; Hu, Jianxiong; Ni, Zhonghua
ABSTRACT: Conventional nuclear magnetic resonance (NMR) instruments are limited by their large volume volume. A miniature NMR spectrometer is reported using a partially enclosed miniature permanent magnet and a low-cost solenoid microcoil probe. The miniature NMR spectrometer uses a sample volume smaller than conventional NMR spectrometers by a factor of 1000. Transverse relaxation times were obtained by the miniature spectrometer using 150 nL of 40 mM copper sulfate, 1 M aqueous sucrose, absolute ethanol, and deionized water. The results demonstrate that high signal-to-noise ratios were obtained. The results were also compared with a commercial NMR spectrometer and suitable accuracy of the laboratory-constructed device was obtained. The miniature NMR spectrometer was employed for the characterization of heated soybean oil. The reported miniature NMR spectrometer is anticipated to have applications for onsite detection.